1998
DOI: 10.1212/wnl.50.3.669
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of tacrine therapy depends on apolipoprotein genotype and gender of the subjects with Alzheimer's disease

Abstract: We studied the effects of apolipoprotein E (APOE) genotype and gender on clinical response to tacrine in patients with mild to moderate Alzheimer's disease (AD). We analyzed data from a previously reported 30-week, double-blind, placebo-controlled trial of tacrine, in which APOE genotypes were determined from previously collected plasma samples. Patients were assigned to placebo or tacrine with daily dosages of 80, 120, or 160 mg/day. The outcome measures were Alzheimer's Disease Assessment Scale-Cognitive Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
2
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(108 citation statements)
references
References 15 publications
6
97
2
3
Order By: Relevance
“…In one study of another cholinesterase inhibitor (galantamine), placebo-treated carriers and noncarriers showed similar cognitive decline over 6 months, 14 while in another similar study carriers showed greater deterioration than noncarriers. 15 A tacrine study that demonstrated less cognitive decline in APOE e4 carriers than in noncarriers, especially in women, over 30 weeks, 16 was consistent with the current 6-month rivastigmine study which shows a tendency for noncarriers taking placebo to have a greater cognitive decline than carriers. The source of these disparate results is not known.…”
Section: Discussionsupporting
confidence: 73%
“…In one study of another cholinesterase inhibitor (galantamine), placebo-treated carriers and noncarriers showed similar cognitive decline over 6 months, 14 while in another similar study carriers showed greater deterioration than noncarriers. 15 A tacrine study that demonstrated less cognitive decline in APOE e4 carriers than in noncarriers, especially in women, over 30 weeks, 16 was consistent with the current 6-month rivastigmine study which shows a tendency for noncarriers taking placebo to have a greater cognitive decline than carriers. The source of these disparate results is not known.…”
Section: Discussionsupporting
confidence: 73%
“…20 Other reports in the literature have not found APOE e4 genotype to influence cognitive response to ChEI therapy. 15,23,24,26,28 Explanations for these inconsistent findings include aspects of study design, such as small sample size, single versus multiple drug dosing, lack of randomization, variable outcome measures used, variable follow-up periods and variable definitions of response to ChEI treatment; pharmacokinetic and pharmacodynamic characteristics of the different ChEIs used; and genetic heterogeneity in the trial populations. Earlier work had suggested that the greater cholinergic deficit 11 and rate of cognitive decline 12 associated with the carriage of APOE e4 might result in a poorer response to ChEI treatment.…”
Section: Apoe Bche and Chei Treatment Response In Admentioning
confidence: 99%
“…Initial reports suggested a better response to tacrine in individuals who were noncarriers of APOE e4, 11,14 particularly in women. 15 However, other researchers have reported that the presence of APOE e4 is associated with improved outcome with ChEI therapy. [16][17][18][19][20] Several studies did not find that APOE genotype influenced treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…These and other concerns about study design of cholinesterase inhibitors have been pointed out by van Gool 108 and Bayer. 109 Interestingly, Farlow et al 110 reported that the treatment outcome of tacrine depends on the apolipoprotein genotype and gender of the subjects with AD. And even the Thal et al 101 study found that ALCAR was more beneficial in a subgroup of patients.…”
Section: Alcar's Neuroprotection Effect On Aging Processes and Relatementioning
confidence: 99%